Urinary Transforming Growth Factor β-1 as a Marker of Renal Dysfunction in Sickle Cell Disease - Emad E. Ghobrial; Hanan A. Abdel-Aziz; Ahmed M. Kaddah; Nesma A. Mubarak (Elsevier, 2016)
Sickle cell disease (SCD) is a genetic disorder that results in deformity of red blood cells. Renal dysfunction affects 5-18% of patients with SCD. To date, few studies have described urinary levels of transforming growth factor β-1 (TGF-β1), which is a marker of fibrosis, as a biomarker in identifying patients at risk of developing renal disease in SCD. The aim of this study is to determine prevalence of sickle cell nephropathy in Egyptian SCD patients. We aimed also to evaluate the association of urinary TGF-β1 with other conventional biomarkers of renal damage in SCD patients to identify a novel renal biomarker for early diagnosis of sickle nephropathy. Methods: We examined 40 SCD patients, 21 with sickle cell anemia, 16 sickle thalassemia, and three with sickle trait. We compared them to 20 control children with matched age and sex. The study was held in the time period between May 2013 and December 2013 in the Hematology Clinic, New Cairo University Children Hospital, Cairo, Egypt. Results: Urinary excretion of TGF-β1 was 7.07 ± 1.91 ng/mL in SCD patients versus 2.23 ± 0.76 ng/mL in control children (p < 0.001). SCD patients had elevated estimated glomerular filtration rate (177.44 ± 35.6 mL/min/1.73 m2), denoting a state of glomerular hyperfiltration. 47.5% of SCD patients had microalbuminuria. Urinary TGF-β1 correlated positively with microalbuminuria and estimated glomerular filtration rate (p = 0.001 and p = 0.018, respectively). Conclusion: We concluded that urinary TGF-β1 may serve as a marker of early renal injury in SCD.